Customer’s perception towards DUNZO delivery service - V.J., DR. MAHESH; P. , HARI (The journal of contemporary issues in business and government, 2020)
The hyping quantity of small - sized shipments and their frequency variation, due to the growth of e-commerce, pose a great challenge to logistics service providers. At the same time, new technologies and contrivances are being developed with the object of hyping the efficaciousness of logistics service providers. Delivered at their position of choice for business this means increased competition. On demand hyperlocal delivery business model connects the transplanted offline business holders to guests through a digital platform. Transplanted offline retailers and service providers got a new development of life for their business ever since the arrival and rise of hyperlocal platforms and Packing the outbound delivery done manually as well as automatically. The findings of the study reveals that the increase in packing, tracking, payment, pricing, schedule delivery having positive linear relationship with respect to customer perception and behaviors. The aim of this paper is to know the perception of customers while delivering a product.